Implications of new-onset atrial fibrillation on in-hospital and long-term prognosis of patients with acute myocardial infarction: A report from the CBD bank study - Yang, Wang-Yang; Lip, Gregory Y. H.; Sun, Zhi-Jun; Peng, Hui; Fawzy, Ameenathul M.; Li, Hong-Wei; , The Cardiovascular Center Beijing Friendship Hospital Database Bank (CBD Bank) study group (Frontiers in Cardiovascular Medicine, 2022)
Background An increase in the incidence of atrial fibrillation (AF) during the acute phase of myocardial infarction (AMI) has been observed. But it is still unclear whether the implications of new-onset AF on in-hospital and long-term prognosis are of similar magnitude. Methods Using data from the CBD Bank study, 3,824 consecutive AMI patients, without prior AF, were analyzed. During the index hospitalization, all patients were monitored by continuous cardiac monitoring, twice daily performed 12- or 18-lead ECGs and timely ECG checks when cardiac symptoms occurred. Follow-up visits were routinely scheduled after discharge. Primary outcomes were all-cause death and cardiovascular death occurring during hospitalization and long-term follow-up. Secondary outcome was MACEs during hospitalization. Results During the median hospital stay of 9.0 (7.0, 11.0) days, new-onset AF was documented in 133 (3.48%) patients; 95 (71.43%) patients had AF attacks within 3 days following AMI. Independent risk factors associated with new-onset AF were older age, larger left atrial diameter, higher level of NT-proBNP, and primary PCI. New-onset AF was found to be significantly associated with in-hospital all-cause death (OR 4.33, 95%CI: 2.37-7.89, P < 0.001), cardiovascular death (OR 4.10, 95%CI: 2.18-7.73, P < 0.001), and MACEs (OR 2.51, 95%CI: 1.46-4.33, P = 0.001). A total of 112 new-onset AF and 3,338 non-AF patients were followed up for 1,090 (365, 1,694) days after discharge. There was no significant association between new-onset AF and long-term all-cause death (HR 1.21, 95%CI: 0.77-1.92, P = 0.406) or cardiovascular death (HR 1.09, 95%CI: 0.61-1.97, P = 0.764). Conclusion New-onset AF following AMI is strongly associated with an increased risk of adverse in-hospital prognosis, but it does not affect prognosis in those who survive until hospital discharge.